2014
DOI: 10.1007/s12291-013-0401-5
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenoreceptor Agonist Isoproterenol Alters Oxidative Status, Inflammatory Signaling, Injury Markers and Apoptotic Cell Death in Myocardium of Rats

Abstract: Sustained high levels of circulating catecholamines are reported to induce cardiotoxicity. Isoproterenol (ISP), a synthetic catecholamine has been widely employed to induce myocardial injury, though the role of inflammation and apoptosis is not well established. This study was designed to investigate the underlying mechanism of oxidative damage, inflammatory signaling, cell death in ISP induced myocardial infarction in rats. Wistar albino rats were divided in two groups: group I (sham control) and group II (is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 29 publications
(32 reference statements)
4
25
0
Order By: Relevance
“…Inhibitor for superoxide was effective in reducing ischemia‐induced VAs . Sympathetic activation could increase the level of oxidative stress and apoptosis . Our previous study also revealed a possible relevance between the cardiac autonomic nervous system and inflammation .…”
Section: Discussionmentioning
confidence: 65%
“…Inhibitor for superoxide was effective in reducing ischemia‐induced VAs . Sympathetic activation could increase the level of oxidative stress and apoptosis . Our previous study also revealed a possible relevance between the cardiac autonomic nervous system and inflammation .…”
Section: Discussionmentioning
confidence: 65%
“…Isoprenaline is a synthetic catecholamine and betaadrenergic receptor agonist that upon oxidation, generates highly toxic free radicals and stimulates membrane phospholipids peroxidation and severe myocardial membrane damage. It is reported that high levels of circulating catecholamines cause cardiac toxicity (19,20). Isoprenaline or isoproterenol-induced myocardial injury represents the occurrence of oxidative damage, lipid peroxidation, LV hemodynamic and function changes following hypertrophy, inflammatory cells infiltration, fibrous and tissue necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Isoprenaline-induced infarction, causes significant metabolical and morphological disorders in the heart muscle of laboratory animals, particularly rats, and shows biochemical and structural changes leading to cell damage and necrosis. Morphological changes observed in the coronary arteries may be justified by the mismatch between the oxygen supply and cardiac muscle demands after coronary hypotension and over activity of cardiac muscle result from isoprenaline (20). Studies have shown that the capacity to secrete catecholamine in response to stimuli such as exercise, hypoglycemia and hypoxia is very high (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISO, a β-agonists, which propel heart rate acceleration, can expand blood vessels and increase the pulse pressure, but large doses of ISO can cause the increase of myocardial oxygen consumption and sharp decline in myocardial blood flow and MI injury [39,40]. And this injury was similar to the process of acute MI in human [42]. And this injury was similar to the process of acute MI in human [42].…”
Section: Discussionmentioning
confidence: 99%